EDUCATION REFORM - AN IMPORTANT ASPECT OF SOCIAL POLICY OF THE MODERN STATE - M. Bolgova (Вестник университета)
The main directions of the reform of higher education in the Russian Federation. The letter explains the purpose and prospects of modernization of higher education and the impact on society. Considered effective forms and methods of management. Allocated social problems facing higher education today.